Analisis Pemahaman Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Melalui Preferensi Risiko Sebagai Variabel Moderasi - Retno Wulandari (Vokasi : Jurnal Riset Akuntansi, 2020)
The purpose of the article is to test its effect and to analyze the understanding variables and tax sanctions on tax compliance with risk preference as a moderating variable regis-tered at KPP Malang Utara. Collecting data using a questionnaire distributed to WP with a purposive sampling approach that has reported SPT. The data technique used is multiple linear regression analysis and moderation analysis of the absolute difference value test approach. The results state that understanding and sanctions affect WP com-pliance. Risk preferences are also capable of modifying understanding and sanctions.